Binaphthyl luminophores with triphenylsilyl groups: sign inversion of circularly polarized luminescence and circular dichroism. Issue 44 (3rd November 2016) - Sato, Takuya; Tajima, Nobuo; Ueno, Hiroki; Harada, Takunori; Fujiki, Michiya; Imai, Yoshitane
Abstract: C 2 -symmetric binaphthol derivatives bearing two bulky C 3 -symmetric triphenylsilyl side groups, open-style 3, 3′-bis(triphenylsilyl)-1, 1′-bi-2-naphthol and closed-style 3, 3′-bis(triphenylsilyl)-1, 1′-binaphthyl-2, 2′-diyl hydrogenphosphate, emit circularly polarized luminescence (CPL) in the near-UV region when dissolved in chloroform and embedded into a poly(methyl methacrylate) film and KBr crystal. Despite the same axial chirality ( S or R ) of the binaphthol frameworks, the C 3 -symmetric triphenylsilyl side groups induced a sign inversion in the CPL and circular dichroism (CD) signals. The possibility of rotation of the C 2 -axis by the bulky groups determines the sign inversion of CPL and CD signals. Graphical abstract: